ANALISIS METODE SIMPLE MOVING AVERAGE UNTUK ESTIMASI PENDAPATAN TOKO KOSMETIK NANISHOP354 - Nurul Khaerani; Dian Anggraeni; Dikwan Moeis (Yayasan Nusantara Hasana Berdikari, 2023)
Nanishop354 is a business in a field that specializes in selling cosmetics. Predictions of cosmetic sales revenue may change from time to time. Income from sales of cosmetics can be a significant income for individuals or shops selling cosmetic products which can be affected by various factors such as product price, level of demand, competition, marketing effectiveness. The purpose of this research is to design a revenue forecast using the Simple Moving Average method to predict the next month's sales. Sales trends that can be seen from the data and how the Simple Moving Average method can be used to predict future sales. The Simple Moving Average method is an effective tool for analyzing sales data at Nanishop354 cosmetics stores and can help stores make better decisions in improving their business. So that the Nanishop354 store can measure the level of profit earned every month and produce good predictions of cosmetic sales profits.